Beliefs related to the dying process and its impact on end-of-life care in the Marma community of Bangladesh: A qualitative study - Mroy, Wai Wai; Bhuiyan, AKM Motiur Rahman; Ibne Towhid, Muhammad Ibrahim; Chowdhury, Mostofa Kamal; Ahmed, Nezamuddin; Haque, Md Atiqul (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Marma indigenous community in Bangladesh has a unique culture with its religion, culture, language, and tradition. To provide appropriate healthcare and end-of-life support, healthcare providers must know their beliefs and customs near and after death. We explored the beliefs related to the dying process and its impact on end-of-life care in the Marma community of Bangladesh. Methods: This cross-sectional qualitative study used an open-ended interview schedule for in-depth interviews. Twenty-six interviewees were selected purposively from the Marma community of Bandarban district to represent a population of different ages with varied experiences and religious knowledge. After each in-depth interview, all field notes and audio records were transcribed verbatim, and qualitative content analysis was done to construct the themes. Results: After analysis, the generated theme indicated a ‘reflection of previous Karma (the sum of a person's actions)’ within the Marma community. This theme is based on three categories: 'state of the body and mind’, ‘care of a dying person’, and ‘beliefs on the dying process’. Conclusion: Death is inevitable for all of us, but suffering in death is not desired. Like other communities around the world, the Marma community also holds its own beliefs and practices regarding end-of-life care related to death. The death of a person in his own house is considered a good death within the Marma community. In the traditional death ritual practices of the Marma community, palliative care in the form of end-of-life care has the potential to enhance the quality of life, alleviate suffering, and enable a peaceful passing with dignity. angabandhu Sheikh Mujib Medical University Journal 2023;16(3): 144-151